Pengaruh Penggunaan Media Pembelajaran Visual terhadap Minat Belajar Siswa dalam Pembelajaran Akidah Akhlak - Barianto, Jeb; Hasrinal, Hasrinal; Nasution, Eline Yanty Putri (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
The background of the problem in this research is the lack of students’ learning interest, the lack of visual learning media, the lack of encouragement from the environment to increase student learning objectives in learning Aqidah Akhlak. This research problem is: (1) whether there is an influence of the use of visual learning media on students’ learning interest; (2) how much influence the use of visual learning media has on student learning interest. The purpose of this study is to determine the effect of visual media variabel (X) on learning interesrt (Y). In this study, data analysis used quantitative methods, namely by testing simple linear regression data instruments, and testing hypotheses data collection techniques using questionnaires by distributing questionaires to 7 respondents in class VII student of Mutiara Al-Madani middle school based on the results of the study, it can be concluded that there is a  positive and significant influence between the variable use of visual learning media on students’ learning interest in Aqidah Akhlak learning as evidenced by t count t table 3.409 2,571, while the magnitude of the influence between the use of visual learning media on student learning interest Aqidah Akhlak learning is 69,8%.